2021
DOI: 10.3390/ijerph18020706
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Emergency Management of Avulsed Teeth among Italian Dentists-Questionnaire Study and Next Future Perspectives

Abstract: (1) Background: In Italy, about one fourth of all schoolchildren experience a trauma to the permanent dentition. Management of avulsion trauma is challenging and requires adherence to clinical protocols. The aim of this study was to investigate the management knowledge of avulsed teeth among Italian dentists and to promote the guidelines’ dissemination through the use of new social media. (2) Methods: The survey was carried out during the COVID-19 lockdown in Italy (March–May 2020). The questionnaire was sent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Managing complex injuries requires a holistic approach that involves different dental professionals at different time points to guarantee the functionality and aesthetics of trauma areas. 6,[34][35][36] This paper focused on the management of transverse root fractures in dental trauma. Epidemiology and classification of transverse root fractures, as well as the physiological responses to healing, emergency management and clinical protocols were presented.…”
Section: Discussionmentioning
confidence: 99%
“…Managing complex injuries requires a holistic approach that involves different dental professionals at different time points to guarantee the functionality and aesthetics of trauma areas. 6,[34][35][36] This paper focused on the management of transverse root fractures in dental trauma. Epidemiology and classification of transverse root fractures, as well as the physiological responses to healing, emergency management and clinical protocols were presented.…”
Section: Discussionmentioning
confidence: 99%
“…As avulsion is a dental emergency situation, prompt management of the avulsed tooth ensures better prognosis. A study conducted by Mazur et al in 2021 16 among Italian dentists showed that the proper management protocol of avulsed tooth was not well understood by the participants and the same findings were revealed by a study done among the Nepalese dentists. 17 A study conducted by Pradhan et al among the Nepalese school teachers also revealed that the participants lacked adequate knowledge about emergency management of dental trauma.…”
Section: Discussionmentioning
confidence: 73%
“…A study conducted by Mazur et al. in 2021 16 among Italian dentists showed that the proper management protocol of avulsed tooth was not well understood by the participants and the same findings were revealed by a study done among the Nepalese dentists 17 . A study conducted by Pradhan et al.…”
Section: Discussionmentioning
confidence: 83%
“…Management of tooth injuries is a treatment that requires multidisciplinary cooperation of many specialists, which is required over a relatively long period of time [4][5][6]. As part of planning such a therapeutic procedure, which requires, inter alia, precise and timed observations, photobiomodulation can be included for use at various stages of the treatment of dental injuries.…”
Section: Introductionmentioning
confidence: 99%